2016
DOI: 10.1002/anie.201605909
|View full text |Cite
|
Sign up to set email alerts
|

Highly Luminescent Cesium Lead Halide Perovskite Nanocrystals with Tunable Composition and Thickness by Ultrasonication

Abstract: We describe the simple, scalable, single-step, and polar-solvent-free synthesis of high-quality colloidal CsPbX (X=Cl, Br, and I) perovskite nanocrystals (NCs) with tunable halide ion composition and thickness by direct ultrasonication of the corresponding precursor solutions in the presence of organic capping molecules. High angle annular dark field scanning transmission electron microscopy (HAADF-STEM) revealed the cubic crystal structure and surface termination of the NCs with atomic resolution. The NCs exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

26
591
4
14

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 657 publications
(652 citation statements)
references
References 33 publications
26
591
4
14
Order By: Relevance
“…[17] Recent studies have shown that nanocrystalline perovskites exhibit enhanced PLQYs and offer tunable optical properties not only through their constituent ions but also through their size. [3,[8][9][10][11]15,18,19] Quantum size effects, as illustrated in Figure 1a, have been extensively investigated in conventional semiconductor nanocrystals such as metal chalcogenides and utilized for a wide range of applications during the last two decades. [20] As the size of the nanocrystals approaches the exciton Bohr radius of the material, quantum confinement effects start to influence the excitonic wave function and the energetic states of the exciton, leading to blueshifted photoluminescence (Figure 1a).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[17] Recent studies have shown that nanocrystalline perovskites exhibit enhanced PLQYs and offer tunable optical properties not only through their constituent ions but also through their size. [3,[8][9][10][11]15,18,19] Quantum size effects, as illustrated in Figure 1a, have been extensively investigated in conventional semiconductor nanocrystals such as metal chalcogenides and utilized for a wide range of applications during the last two decades. [20] As the size of the nanocrystals approaches the exciton Bohr radius of the material, quantum confinement effects start to influence the excitonic wave function and the energetic states of the exciton, leading to blueshifted photoluminescence (Figure 1a).…”
mentioning
confidence: 99%
“…Similarly, perovskite nanocrystals of reduced dimensionality exhibit quantum confinement effects, as shown for the case of nanoplatelets in 2015. [8][9][10]21,22] Despite recent advances, an accurate understanding of thickness-and dimensionality-dependent optical properties of perovskite nanocrystals still proves elusive due to difficulties in the controlled syntheses and characterization of their dimensions. Additionally, while many recent publications present perovskite nanocrystals, most of these show negligible or no quantum confinement.…”
mentioning
confidence: 99%
“…Tong et al reported high-quality colloidal CsPbX 3 (X = I, Br, and Cl) perovskite nanocrystals (NCs) [103]. The synthesis was based on direct tip sonication of precursor mixtures under ambient atmospheric conditions.…”
Section: Growth Of Fully Inorganic Halide Perovskite Single Crystalsmentioning
confidence: 99%
“…1. While the electron beam irradiation effect on the 3D halide perovskite materials have been investigated [5][6][7][8][9], studies on 2D halide perovskites are lacking.Herein we present dynamic surface modification on a BA2MA2Pb3I10 (n=3) 2D perovskite with BA (butyl-ammonium, CH3(CH2)3NH3+) working as QW barrier molecules induced by electron beam in transmission electron microscope. We observed various surface dynamics in atomic level under electron irradiation such as lateral growth in c planes of polytypic PbI2 with 3R, 4H and 2H structures at the edge surface of the 2D perovskite accompanied with simultaneous annihilation of surface plane as can be seen in Fig.…”
mentioning
confidence: 99%
“…1. While the electron beam irradiation effect on the 3D halide perovskite materials have been investigated [5][6][7][8][9], studies on 2D halide perovskites are lacking.…”
mentioning
confidence: 99%